Micologia forense : a dinâmica da microbiota fúngica na investigação do período post mortem - Moreira Filho, Renato Evando (2008)
With developing of forensic observations, certain species of insects and microorganisms were described as indicators of periods of the degradation of the body. However, the literature is still scarce in the field of Forensic Mycology. It was investigated the microbiological characteristics of fungi presence in the post mortem change, as well as, it esteemed the value of the mycology exams in the study. 400 collections was accomplished in 60 human bodies (34 of the bloated stage, 06 of the putrefaction stage and 20 of the skeletonization stage) at the Fortaleza city morgue and public cemeteries in the state of Ceará, The picked material was analyzed through macro/microcharacteristics and specific biochemical tests. Ally to such analyses, was also accomplished the test of the perforation of the hair in vitro in hair of corpses in the bloated stage and in hair of healthy adults. The material gathered was analyzed at the Specialized Medical Mycology Center of the Federal University of Ceará. With the anthropological results, it was observed that male, in the interval of the 31 to the 40 years, was more commonly attacked, being the capital (Fortaleza) the more involved in the number of deaths. In the bloated stage, among the identified filamentous fungi, the presence of four orders was observed: Order Eurotiales (63 isolated Aspergillus spp and 21 isolated Penicillium spp), Order Mucorales (4 Mucor spp), Order Hypocreales (2 Acremonium spp, 1 Trichoderma spp and 1 Fusarium spp) and Order Saccharomycetales (2 Geotrichum spp). In the yeast distribution, it was observed the orders:Saccharomycetales (44 Candida spp) and Tremellales (5 Trichosporon spp). In the putrefaction stage, it was isolated the following orders: Eurotiales (Penicillium spp 2 and Aspergillus 2) and Hypocreales 1 (Acremonium spp). Regarding the yeasts, it was just isolated the Order Saccharomycetales (Candida spp 3). In the eskeletonization stage, the following orders were observed: Order Eurotiales (Aspergillus spp 22 and Penicillium spp 18), Order Mucorales (Mucor spp 10) and Order Hypocreales (Acremonium spp 2 and Trichoderma spp 1). Regarding the yeasts, two orders were found: Tremellales (Trichosporon spp 1) and Saccharomycetales (Candida spp 1). In the hair perforation test in vitro, it was positive in the bloated stage, differing of healthy adults,where the test was negative. For conclusion, Forensic Micology is still a rich field in data and fungi can come to be a tool in the aid of human post mortem diagnosis.